Methodology and Results of Teaching Competences for Teaching English to Children at CIEX - Tornés, Nora (CIEX JOURNAL, 2016)
This study was chosen because when the researcher faced difficulties teaching English to children this situation brought questions to improve the performance with them. The relevance of this study lies on the fact that there is not a lot of researching for young learners in the field of language. This research is focused on teaching English to children. It studies teaching competences, the communicative competence developed in class, strategies and activities that teachers use and the promotion of moral values. This research also offers some suggestions for improving the previous factors in teacher’s competences in the field of teaching English to children.